Pengabulan Permohonan Penundaan Kewajiban Pembayaran Utang (PKPU) PT Emco Asset Management (Studi Putusan Nomor : 78/Pdt.Sus PKPU /2020/PN/Niaga.Jkt.Pst) - Yulisa, Farah Amalia; Putra, Setia; Samariadi, Samariadi (Peneliti.net, 2025)
Postponement of Debt Payment Obligations (PKPU) or surseance van betaling is a period of time granted by law through a decision of a Commercial Court Judge. In essence, the purpose of postponing debt payment obligations is to make peace between debtors and their creditors and to prevent debtors who have or will experience insolvency from being declared bankrupt. The process of postponing debt payment obligations in cases with Decision Number 78/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst has paid much attention to the legal subjects who are authorized to submit a request for a postponement of debt payment obligations. The type of research used by the author is a normative legal research method normative legal. Based on the results of the research and discussion, it can be seen that the legal subject who is authorized and has the legal standing to submit an application for a postponement of debt payment obligations against the securities company PT. Emco Asset Management is the Financial Services Authority (OJK) in accordance with Article 55 of Law Number 21 of 2011 concerning the Financial Services Authority. Contrary to decision Number 78/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst, the party submitting the application is the creditor. Simple proof applies to applications for a declaration of bankruptcy.